Modeling revenge and avoidance in the mobile service industry: moderation role of technology anxiety. Issue 15 (10th December 2021) - Hsu, Li-Chun; Wang, Kai-Yu; Chih, Wen-Hai; Lin, Wei-Ching
ABSTRACT: This research investigates the impact of service failure severity on consumers' negative emotion (anger) and coping behaviors (revenge and avoidance) in the context of mobile application service failure. It also identifies the moderating role of technology anxiety on the relationship between service failure severity and blame attribution. The sample for this study consisted of users who had experienced a mobile application service failure in Taiwan. This study distributed online surveys to potential respondents via MySurvey, an online survey distribution platform. Seven hundred and thirty-one mobile application users participated in this study. This study adopted Structural Equation Modeling to test the research hypotheses. The results showed that service failure severity positively affected blame attribution and, thus, amplified the anger of negative emotion. Revenge and avoidance occurred. Technology anxiety had a moderating effect on the relationship between service failure severity and blame attribution.